Naphthol as A Biological Monitoring on Naphthalene Exposure in Workers - Arriz Akbar Sukadi; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Introduction: Naphthalene is one of the chemicals that are widely used throughout the world, such as aircraft fuel, camphor, insecticides, and colouring agents in cosmetics. Exposure to naphthalene can cause health problems ranging from dermatitis and haemolytic anaemia to even the possibility of cancer of the respiratory tract, therefore it is necessary to carry out biological monitoring of workers at risk. The aim of this study is to find out which is the simplest and most reliable biomonitoring to use based on an evidence-based literature review. Methods: Literature search was conducted through electronic databases from PubMed, ProQuest, and Cochrane. The keywords used are worker, naphthalene, and biomonitoring. Initially, 273 articles were obtained, but after going through a selection process and manual search, seven articles were examined. Results: Based on the selected evidence-based literature, it was found that there was an increase in the level of naphthol in the urine in workers exposed to naphthalene who were examined during pre-shift and post-shift. Conclusion: Naphthol concentration in urine can be a non-invasive, easy, and reliable biomonitoring exposure of naphthalene. Although it is currently not possible to do this in Indonesia, this study shows the importance of biomonitoring to prevent occupational diseases due to this exposure.